THE EVIL GOD CHALLENGE – A RESPONSE. Issue 40 (9th April 2015) - Ward, Keith
Abstract : I argue that the co-existence of omnipotence, omniscience, and total evil forms an inconsistent triad. An omniscient being will know what it is like for anyone to feel pain, and since pain is undesirable, will not freely create pains which it would have to share. An omnipotent being would choose to be rational, and a purely rational being would choose what it believes to be good. It would in fact choose to be of supreme value, and thus would necessarily contain all compossible values, including those of friendship and love. Therefore an omnipotent omniscient being cannot be evil.